2014
DOI: 10.1186/1752-1947-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase-negative anaplastic large cell lymphoma with extranodal involvement of the thigh muscle: a case report

Abstract: IntroductionAnaplastic large cell lymphoma is a rare type of non-Hodgkin lymphoma. The most common extranodal sites of anaplastic large cell lymphoma are skin, subcutaneous tissue, bone, lung, and gastrointestinal organs. The involvement of the skeletal muscle has been described rarely in extranodal anaplastic large cell lymphoma.Case presentationAn 89-year-old Japanese man visited our hospital with a three-month history of swelling of his left thigh and slight fever. The swelling had rapidly enlarged and beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Our patient presented with severe pain and B‐symptoms (fever and night sweats), and with primary skeletal muscle CD30‐positive, ALK‐negative ALCL. The patient died 2 months after her admission, and similar survival of affected cases has been reported previously . However, some reports indicated that patients with primary skeletal muscle ALCL responded to systemic chemotherapy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our patient presented with severe pain and B‐symptoms (fever and night sweats), and with primary skeletal muscle CD30‐positive, ALK‐negative ALCL. The patient died 2 months after her admission, and similar survival of affected cases has been reported previously . However, some reports indicated that patients with primary skeletal muscle ALCL responded to systemic chemotherapy.…”
Section: Discussionsupporting
confidence: 79%
“…The patient died 2 months after her admission, and similar survival of affected cases has been reported previously. 5,12 However, some reports indicated that patients with primary skeletal muscle ALCL responded to systemic chemotherapy. Most of these patients had the aforementioned favorable prognostic factors (ALK-positive, young age).…”
Section: (A) (B)mentioning
confidence: 99%
“…Unfortunately, our patient died of multiple organ failure 4 weeks after her first visit to our hospital and similar survival of such cases has been reported previously. [ 4 , 5 ]…”
Section: Case Reportmentioning
confidence: 99%
“…[ 4 ] Extranodal involvement of skeletal muscles in ALCLs is extremely rare. [ 5 ] Here, we present a rare case of ALK− ALCL of multiple extranodal involvement, especially the whole body skeletal muscles, with the aim to share the imaging features of the ALCL including magnetic resonance imaging (MRI) and 18 F-fluorodeoxyglucose positron emission tomography–computed tomography ( 18 F-FDG PET–CT). Imaging findings from a review of relevant literature are presented.…”
Section: Introductionmentioning
confidence: 99%
“…ALK-negative anaplastic large cell lymphoma (ALK-ALCL) is a rare CD30+ T-cell neoplasm involving both lymph nodes and extranodal sites, often presenting with B symptoms and advanced stage disease [1]. Primary involvement of the skeletal muscles is extremely rare in adults and has been associated with rapid dissemination and poor prognosis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%